Carrier Deformability in Drug Delivery - Jose Morilla, Maria; Lilia Romero, Eder (Current Pharmaceutical Design, 2016)
Deformability is a key property of drug carriers used to increase the mass penetration across the skin without disrupting the lipid barrier. Highly deformable vesicles proved to be more effective than conventional liposomes in delivering drugs into and across the mammalian skin upon topical non occlusive application. In the past five years, highly deformable vesicles have been used for local delivery of drugs on joint diseases, skin cancer, atopic dermatitis, would healing, psoriasis, scar treatment, fungal, bacteria and protozoa infections. Promising topical vaccination strategies rely also in this type of carriers. Here we provide an overview on the main structural and mechanical features of deformable vesicles, to finish with an extensive update on their latest preclinical applications.
Keywords: Topical drug delivery